Penerapan Model Pembelajaran Mastery Learning (Belajar Tuntas) Dalam Meningkatkan Prestasi Belajar Akidah Akhlak - Syarifuddin Syarifuddin; Zubaidah Zubaidah; Khairiah Khairiah (At-Ta'lim : Media Informasi Pendidikan Islam, 2022)
Abstract: Application of Mastery Learning Model (Complete Learning) in Improving The Learning Achievement of Akhlak Creed. Students have had difficulty in improving morally advanced learning achievements because teachers are not able to develop learning models. The purpose of this paper is to map the achievements of students learning. Using descriptive qualitative methods. The findings show (1) the form of student achievement has not been optimal because teachers are less able to apply the mastery learning model; (2) the relationship of applying the mastery learning model. The more effective the application of the learning model, the higher the achievements achieved by students; (3) the application of mastery learning (complete learning) model affects the improvement of student achievement in learning morals. Then it can be concluded that the application of the mastery learning model (complete learning) can improve the achievements of students learning moral beliefs. With this can be recommended to the institution. Abstract: Penerapan Model Pembelajaran Mastery Learning (Belajar Tuntas) dalam Meningkatkan Prestasi Belajar Akidah Akhlak. Siswa telah mengalami kesulitan dalam meningkatkan prestasi belajar akidah akhlak dikarenakan guru guru tidak mampu mengembangkan model pembelajaran. Tujuan tulisan ini adalah untuk memetakan prestasi siswa belajar. Menggunakan metode kualitatif diskripstif. Temuan menunjukkan (1) bentuk prestasi siswa belum optimal disebabkan guru kurang mampu menerapkan model pembelajaran mastery learning; (2) hubungan penerapan model pembelajaran mastery learning. Semakin efektif penerapan model pembelajaran, maka semakin tinggi prestasi yang dicapai siswa; (3) penerapan model pembelajaran mastery learning (belajar tuntas) mempengaruhi peningkatan prestasi siswa belajar akidah akhlak. Kemudian dapat disimpulkan bahwa penerapan model pembelajaran mastery learning (belajar tuntas) dapat meningkatkan prestasi siswa belajar akidah akhlak. Dengan ini dapat disarankan kepada lembaga pendidikan untuk menerapkan model pembelajaran mstery learning untuk meningkatkan prestasi siswa.